Red Meat Production Forecast and Policy Recommendations in Line with 2023 Targets in Turkey - Akgül, Sevim; YILDIZ, Şaduman (European Journal of Multidisciplinary Studies, 2016)
There is a certain delay between the manufacturers due to red meat production decisions, give producers in price compared to the previous year, the production decision, this situation leads to a surge in the amount of consumption of red meat and red meat prices. Individuals in a balanced diet, especially red meat consumption, are considered to be of great importance to supply and economic development criteria. An economic variable values will be in the future, according to the cyclical state of the economy, always involves uncertainty. This uncertainty also applies to the red meat production. In this study, consumption of red meat to Turkey for estimation, Box-Jenkins forecasting models are used. Between the years 2016-2023 red meat production forecasts are made regarding Turkey in the framework of this model. In line with the objectives of 2023, Turkey to increase the consumption of red meat, is given to policy proposals.
Keywords: Turkey's Red Meat Production, Box-Jenkins Model